Pengaruh Pemberian Aromaterapi Lavender Terhadap Tingkat Kecemasan Pada Akseptor Kb Implan Di Puskesmas Haurpanggung Kabupaten Garut Tahun 2023 - Nisa, Khoerun; Handayani, Handayani (Lembaga Publikasi Ilmiah Nusantara, 2023)
Haurpanggung Health Center in 2022 the coverage of MKJP use for implantable contraception is 405 people (6.61%). The fear of pain during implant insertion is a major source of anxiety for many clients and is the reason for the low coverage of implants. One way nonpharmacology reduces anxiety levels in a person when implants are installed is with lavender aromatherapy. Purpose; The purpose of this study was to determine the effect of lavender aromatherapy on anxiety levels in implant birth control acceptors. Methodology: this study used quasi-experiments with pretest posttest one group design. The population in the study of all implant acceptors was 30 orals. The sample in the study used total sampling. The instruments used are HRS-A observation sheets and technical instructions for giving lavender aromatherapy. Data analysis using paired sample test. Research Results: Anxiety of prospective acceptors of implantable birth control before lavender aromatherapy was 14.40 and after intervention 9.57. Bivariate results showed a p-value of 0.000 Conclusion: There is an effect of lavender aromatherapy on anxiety levels in implanted birth control acceptors. Suggestion: It is expected to be information and increase knowledge on prospective implantable birth control acceptors to use non-pharmacological management in reducing anxiety by using lavender aromatherapy